Impact of platelet phenotype on myocardial infarction. (February 2015) - Gabbasov, Zufar; Sabo, Jan; Petrovic, Daniel; Martell-Claros, Nieves; Zagatina, Angela; Mrdovic, Igor; Ciccocioppo, Rachele; Cangemi, Giuseppina Cristina; Klimas, Jan; Kruzliak, Peter
Abstract In acute myocardial infarction patients the injured vascular wall triggers thrombus formation in the damage site. Fibrin fibers and blood cellular elements are the major components of thrombus formed in acute occlusion of coronary arteries. It has been established that the initial thrombus is primarily composed of activated platelets rapidly stabilized by fibrin fibers. This review highlights the role of platelet membrane phenotype in pathophysiology of myocardial infarction. Here, we regard platelet phenotype as quantitative and qualitative parameters of the plasma membrane outer surface, which are crucial for platelet participation in blood coagulation, development of local inflammation and tissue repair.